CERITA RAKYAT 'ASAL-USUL NAMA DUKUH PANTARAN' SEBAGAI PEMBENTUK LITERASI MORAL - Jeni Nur Cahyati (Faculty of Cultures and Languages UIN Raden Mas Said, 2021)
This study aimed at describing the role of the folklore entitled Asal-usul Nama Dukuh Pantaran for building moral literacy. This is a qualitative-descriptive study with data in the form of words, phrases, clauses, and sentences containing moral literacy values found in the folklore. For collecting the data, observation, interviews, and documentation techniques were employed. For data validation, source triangulation was applied whereas for data analysis, it used interactive model. The result of this research shows that the folklore Asal-usul Nama Dukuh Pantaran contains the components that make up moral literacy competence, namely ethical sensitivity, ethical reasoning, and moral imagination. Ethical sensitivity can be seen in the practices of religious and social attitudes. Meanwhile, ethical reasoning on religious and social attitudes can be identified regarding the usefulness and nature of caring. On the other hand, moral imagination is shown by the nature of relief in accepting decisions. With these three components, the folklore Asal-usul Nama Dukuh Pantaran has the potential as the source for building moral literacy.